PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, TIPE INDUSTRI DAN KINERJA LINGKUNGAN TERHADAP ENVIRONMENTAL DISCLOSURE - Oki Yacintya Dewi, Ida Ayu Putu; Yasa, Gerianta Wirawan (E-Jurnal Akuntansi; Vol 20 No 3 (2017), 2017)
Environmental disclosure is the disclosure of information relating to the environment in the company's annual report. Environmental Related Research Disclosure is growing rapidly, but still resulted in findings that diverse. This study aims to identify and test the effect of firm size, profitability, industry type, and environmental performance of the environmental disclosure. The population in this study are public corporations non-financial listed on the Indonesia Stock Exchange (BEI) and registered as a participant PROPER years 2012-2015. The sampling method in this study using a nonprobability sampling methods with a purposive sampling technique. The unit of analysis is the company's annual report and list of participant PROPER years 2012-2015, totaling 208 observations. The data analysis method used is multiple linear regression analysis. The results show that firm size, industry type and positive effect on the environmental performance environmental disclosure. However, profitability has no effect on environmental disclosure.
Keywords: Environmental Disclosure, Firm Size, Profitability, Industry Type, Environmental Performance, PROPER